Ethylene vinyl acetate co-polymer degradation by environmental microbes - Wong, Bryan Jun Long (Nanyang Technological University, 2022)
Delamination of EVA encapsulant is one of the more difficult and crucial steps in the recycling of photovoltaic modules. Currently, several methods that are hazardous and highly energy-intensive such as disintegration and chemical dissolution are being adopted by industries to delaminate EVA encapsulants. This study explores the possibility of using environmental microbes as a sustainable alternative to conventional methods in delaminating the EVA encapsulant. Commercial crosslinked EVA polymeric sheets were used in this study to be biodegraded in liquid media using Rhodococcus ruber, (R.ruber) standard strain as well as environmental microbial samples obtained from NTU, Semakau landfill, and MacRitchie reservoir. The biodegradation effects of the microorganisms on the EVA samples were evaluated using different techniques such as attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), measurement of optical density (OD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). Carbonyl index (CI) calculation obtain from FTIR spectra revealed a reduction in CI levels in the EVA sheets after 40days of degradation. ATR-FTIR measurements also captured biofilm formations by R.ruber when biodegrading the EVA sheets. Overall results obtained showed that environmental microbial samples fair better at degrading the EVA polymer than standard R.ruber microbes. Among them, microbial samples from NTU showed the highest potential when compared to other environmental strains. When tested for the presence of laccase and esterase enzymes using Remazol brilliant blue R (RBBR) dye and Tween 20 as substrates in agar-based experiments, environmental strains from NTU were tested positive for both esterase and laccase production while R.ruber did not exhibit any production of the said enzymes.